PENINGKATAN MINAT DAN PRESTASI BELAJAR MAHASISWA PGSD PADA MATA KULIAH MEDIA PEMBELAJARAN PKn MELALUI TEKNIK BRAINSTORMING MENGGUNKAAN MEDIA TIGA DIMENSI (3D) - Aji Heru Muslim; Sri Harmianto (Khazanah Pendidikan, 2016)
This study aimed to improve students’ learning interest and achievement in the subject of Civics Education Learning Media through Brainstorming Techniques using three-dimensional media. This research was classified as a classroom action research consisting of 2 cycles. The object was fourth semester students (class A), Department of Elementary School Teacher Education, University of Muhammadiyah Purwokerto. The students’ number was 45 persons. For analyzing students’ learning interest, the instruments used in the data collection process were questionnaire sheet, the data analysis was done using descriptive qualitative. The indicator was improvement of students’ learning interest and achievement. The research results showed it could improve the students’ learning interest and achievement in the subject. It could be proven by the improvement of students’ learning interest and achievement. In the first cycle, students’ learning interest was 65.36%. It was 77.44% in the second cycle. So, the average score of students’ learning interest was excellent. In addition, it could also improve students’ learning achievement. In the first cycle, the improvement was 71.43%. It was 91.43% in the second cycle. Keywords : Interest, Achievement, Learning Media of Civics Education, Brainstorming Technique and Three Dimensional Media.